2022
DOI: 10.3389/fpls.2022.988442
|View full text |Cite
|
Sign up to set email alerts
|

Root exudates and chemotactic strains mediate bacterial community assembly in the rhizosphere soil of Casuarina equisetifolia L

Abstract: Rhizosphere bacterial diversity and community structure are important factors involving in plant growth. However, the exact process of how plant rhizosphere bacterial community structures is assembled remains unclear. To investigate the role of bacterial chemotaxis to rhizosphere secretions in the establishment of rhizosphere microbial community in Casuarina equisetifolia, we screened bacteria strains derived from the rhizosphere of Casuarina equisetifolia L. using top three chemicals of the plant root exudate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Meanwhile, low concentrations of 2,4-DTBP (60 mM) can aggregate rhizosphere soil bacteria, e.g., Bacillus cereus strain CP1, Pseudomonas sp. and Enterobacter hormaechei strain AMS-38 (Huang et al, 2018;Lin et al, 2022). Cui et al (2022) also found that microbial biomass was stimulated with the addition of 0.5 mM 2,4-DTBP and inhibited with the addition of 2.0 mM 2,4-DTBP.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Meanwhile, low concentrations of 2,4-DTBP (60 mM) can aggregate rhizosphere soil bacteria, e.g., Bacillus cereus strain CP1, Pseudomonas sp. and Enterobacter hormaechei strain AMS-38 (Huang et al, 2018;Lin et al, 2022). Cui et al (2022) also found that microbial biomass was stimulated with the addition of 0.5 mM 2,4-DTBP and inhibited with the addition of 2.0 mM 2,4-DTBP.…”
Section: Discussionmentioning
confidence: 91%
“…Meanwhile, low concentrations of 2,4-DTBP (60 μM) can aggregate rhizosphere soil bacteria, e.g., Bacillus cereus strain CP1, Pseudomonas sp. and Enterobacter hormaechei strain AMS-38 ( Huang et al., 2018 ; Lin et al., 2022 ). Cui et al.…”
Section: Discussionmentioning
confidence: 99%
“…Certain root exudate metabolites change the PGPR growth, swarming, and biofilm formation. 2,4-Di-tert-butylphenol and methyl stearate showed strong chemotaxis in the rhizosphere bacteria of Casuarina equisetifolia L. [ 10 ]. In this study, methyl stearate and 2,4-di-tert-butylphenol promoted NRCB010 swarming ( Figure 3 C), which confirms previous results.…”
Section: Discussionmentioning
confidence: 99%
“…Colonization, chemotaxis, and biofilm formation by PGPR are induced by the root exudates and certain metabolites [ 3 , 5 , 10 ]. Root exudates are composed of low-molecular-weight carbon compounds that are passively or actively exuded from plant roots.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation